Prevalence and Pattern of Self-Medication among Undergraduate Medical Students - Sivaranjan R, SrinidhiSrikanth, Rock Britto, Rajaram S, Elango S, Shilpa Charles D, Shyamala Priya M, (International Journal of Innovative Research in Medical Science, 2017)
Background: Self-medication is becoming a Universal entity wherein, drugs are given over-the-counter without prescription, providing a low cost alternative for people, irrespective of rural-urban differences[1], which might be horrendous when not applied with proper medical knowledge. It enjoys a paramount significance among medicos as they are the future practitioners of medicine with easy access to drugs. Aim: To assess the prevalence and pattern of self-medication practice among undergraduate medical students. Material and Methods: A cross-sectional questionnaire-based study was conducted among the undergraduate medical students of a tertiary care medical college in Tamil Nadu, India during February to March 2016. Results: 400 students accepted for the study and took up the given questionnaire. 9 incomplete questionnaires were expelled and the remaining 391were analyzed. It was found that 273 (69.8%) respondents practiced self-medication, which was common in females (53.5%) than in males (46.2%).The practice was widely prevalent among the pre final year students (84.3%) followed by final year students (74.6%) and second-year students (48.8%). The main symptoms for seeking self-medication included fever (36.6%), common cold (27.8%), heartburn (16.4%), and abdominal pain (8.4%). Drug groups commonly used for it were analgesics-antipyretics (31.09%), antihistamines (28.9%), antibiotics (22.7%), antacids (16.8%) and antispasmodics (9.5%). On analyzing the reason for self- medication, 52.7% students felt that their illness was not so severe while 34.1% stated previous experience with similar illness, 8.4% cited constrain of time and 4.8% mentioned easy access to drugs. The commonest source of information for self-medication were previous prescriptions (59.7%) and family (19.8%). 35.2% of the students prescribed medication to others. 98.2% respondents felt self-medication practices can be horrendous and 88.7% suggested health education to put an end to self-medication. Conclusion: Our study reflects the prevalence of self-medication among the undergraduate medical students, which can be brought down by the faculty through their efforts to educate and create awareness among the students.